1975
DOI: 10.1111/j.1432-1033.1975.tb21031.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Human Milk β(1 – 4)‐d‐Galactosyltransferase

Abstract: p( 1 -4)-Galactosyltransferase from human milk (the A protein of lactose synthase) has been found to be heterogeneous when fractionated by affinity chromatography against insolubilized a-lactalbumin, using a linear gradient of decreasing N-acetylglucosamine concentration. Three forms were isolated. Molecular weights of the different species, as determined by sodium dodecylsulphate gel electrophoresis, were found to be 38000, 43000 and 50000. The 38000 and 50000 species were studied for their catalytic ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In no instances could proteolytic breakdown products as described by Prieels et al [28] or dimeric components as found by Powell and Brew [29] be detected. Barker already observed that the use of N-acetylglucosamine-derivatized agarose in the main purification step reduced the extent of concomitant proteolytic breakdown of bovine galactosyltransferase [20].…”
Section: Discussionmentioning
confidence: 74%
“…In no instances could proteolytic breakdown products as described by Prieels et al [28] or dimeric components as found by Powell and Brew [29] be detected. Barker already observed that the use of N-acetylglucosamine-derivatized agarose in the main purification step reduced the extent of concomitant proteolytic breakdown of bovine galactosyltransferase [20].…”
Section: Discussionmentioning
confidence: 74%
“…Since the enzyme present in human plasma described herein is very similar to that of the A-protein of lactose synthase present in human milk (Powell & Brew, 1975), yet the molecular weight of the plasma enzyme appears to be nearly twice that of the milk enzyme, the possibility exists that the plasma enzyme may be a precursor for the milk galactosyltransferase. This speculation is supported by the findings (Prieels et al, 1975) that the human milk galactosyltransferase is a heterogeneous population of enzymes with mol.wts. of 38000 to 50000, thought to be a result of proteinase activity.…”
mentioning
confidence: 72%
“…The small molecular weight components of approximately 20 kD most likely represent breakdown products of the enzyme. This assumption, however, is difficult to substantiate experimentally as they are inconsistently found and devoid of enzymatic activity [3,6]. The 'heavy' form of cross-reactive material of approximately 110 kD was also identified in eluates of milk resolved on a Sephacryl S-200 column as sayed for the presence of antigen in fractions by ELISA [18].…”
Section: Discussionmentioning
confidence: 99%
“…Human milk galacto syltransférase activity was found to be homo geneous upon elution from a BioGel P200 column with an apparent molecular weight of 40-42 kilodaltons (kD) [1], Prieels et al [3], however, found considerable heterogeneity on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE): three main forms of 50, 43 and 38 kD, respectively, were detected and attributed to proteolytic degra dation, a phenomenon which was well estab lished and characterized in bovine milk by Magee et al [4][5][6]. In addition, Khatra et al [7] also reported the presence of a 98-or 100-kD galactosyltransférase species in human milk as determined by SDS-PAGE and gel filtration, respectively.…”
Section: Introductionmentioning
confidence: 99%